2013
DOI: 10.1002/j.0022-0337.2013.77.3.tb05477.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Local Anesthesia Education in Turkish Dental Schools

Abstract: The aim of this study was to evaluate differences with regard to local anesthesia education in Turkish dental schools. Questionnaires designed to collect information about local anesthesia education were sent to the heads of the Departments of Oral and Maxillofacial Surgery of seventeen Turkish dental schools. Eleven returned the completed survey for a response rate of 64 percent. It was determined that dental schools begin the theoretical part of their local anesthesia (LA) curricula during the irst half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…In bridging the theory‐to‐practice gaps, various methods are used for teaching preclinical dental local anesthesia. These involve injecting into inanimate objects, such as oranges, chicken legs, and simulation models 7 , 8 . Student‐to‐student administration of first local anesthetic injections has been a traditional method for preclinical training in dental education 9 , 10 .…”
mentioning
confidence: 99%
“…In bridging the theory‐to‐practice gaps, various methods are used for teaching preclinical dental local anesthesia. These involve injecting into inanimate objects, such as oranges, chicken legs, and simulation models 7 , 8 . Student‐to‐student administration of first local anesthetic injections has been a traditional method for preclinical training in dental education 9 , 10 .…”
mentioning
confidence: 99%
“…Likewise, two other studies addressed students’ experiences with anatomic models and found that the students perceived them to be helpful 18 , 19 . Although survey respondents reported being highly satisfied with their existing curricula, many schools are introducing such models 20 , 21 . Marei and Al‐Jandan found that students who trained with a simulation model performed significantly higher on a written test of local anesthesia knowledge than students who received a conventional slideshow presentation 22 …”
Section: Resultsmentioning
confidence: 99%
“…Anatomic models are a promising tool for local anesthesia education and are being introduced in some dental schools 20 , 21 . Sensor‐embedded models have been shown to be a valuable addition in familiarizing students with the ideal injection site locations and orientations, but these models are not in widespread use 19 .…”
Section: Discussionmentioning
confidence: 99%
“…There are studies interfering with the administration and receipt of a local anesthetic injection in current dental educational systems ( 15 - 21 ). However, there is a limited number of studies regarding dental education on serving pain-free local analgesia ( 4 , 22 ).…”
Section: Discussionmentioning
confidence: 99%